Comparison of Gait Parameters Between Individuals with Normal Arch and Flat Arch Conditions among Students at SD Negeri Daleman 01, Nguter, Sukoharjo - Syaifuddin, Muhammad; Syafi'i, Muhammad; Fitriana, Shania Mulya (Journal of Prosthetics Orthotics and Science Technology, 2023)
This study aims to compare gait parameters between the normal arch condition and the flat arch condition in students at SD Negeri Daleman 01, Nguter District, Sukoharjo. A flat foot, which is a common disorder characterized by the loss of arches in the feet, can interfere with walking pattern, cadence, timing, and speed. This study used a comparative approach with a cross-sectional observational analytic research design. The research sample consisted of students aged 7-12 years, with either a normal arch or flat arch condition. Gait parameters were measured using an instrument for assessing gait parameters. Data analysis involved tests for normality and hypothesis testing using the Mann-Whitney test. The results of the study showed a significant difference (p-value < 0.05) in gait parameters between the normal arch condition and the flat arch condition. Students with a normal arch condition demonstrated better gait parameters compared to those with a flat arch condition. Students with a flat arch condition tended to have shorter step lengths, wider step widths, longer ground contact time, and slower walking speeds compared to students with a normal arch condition. Based on the results of this study, it can be concluded that a flat arch condition potentially affects gait parameters in students at SD Negeri Daleman 01, with a p-value < 0.05. This information can be useful for relevant parties in monitoring and addressing gait parameter issues in students with a flat arch condition.